1983
DOI: 10.2307/1130043
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sex-Typing Schemas on Young Children's Memory

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(69 citation statements)
references
References 31 publications
2
66
0
1
Order By: Relevance
“…Perhaps, individuals distort their perceptions and memory of emotions to conform to gender stereotypes. Developmental researchers have found that children frequently distort gender-inconsistent information (e.g., a picture of a man in the kitchen) to gender-consistent information (e.g., a picture of a woman in the kitchen) on memory tasks (Bigler & Liben, 1990Levy & Fivush, 1993;Martin & Halverson, 1983;Welch-Ross & Schmidt, 1996). Similar processes may contribute to stereotypes about gender and emotionality.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, individuals distort their perceptions and memory of emotions to conform to gender stereotypes. Developmental researchers have found that children frequently distort gender-inconsistent information (e.g., a picture of a man in the kitchen) to gender-consistent information (e.g., a picture of a woman in the kitchen) on memory tasks (Bigler & Liben, 1990Levy & Fivush, 1993;Martin & Halverson, 1983;Welch-Ross & Schmidt, 1996). Similar processes may contribute to stereotypes about gender and emotionality.…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive process of assimilation allows schemas to assist in interpreting information from the environment. For instance, new information can be given meaning, missing information can be supplied, and even existing information can be distorted to make it become consistent with existing schemas (e.g., Martin and Halverson 1983). Behavioral changes also enhance schematic consistency; children are able to approach activities they believe fit their schemas while avoiding activities that are not consistent with their gender schemas (Martin 2000;Martin and Halverson 1981).…”
Section: The Traditional View: Gender-differentiated Behaviors Promotmentioning
confidence: 99%
“…Children may use their gender cognitions to "fill in the gaps" in their knowledge, that is, by making assumptions that they share more in common with same-gender peers than they have actually experienced with them. Furthermore, this approach suggests that children will distort or alter memory of the peer's behavior if it does not fit expectations (Bigler and Liben 2006;Martin and Halverson 1983). These issues provide innovative ways to think about the role of gender in peer relationships, and provide testable hypotheses that are worth pursuing.…”
Section: Theoretical Significancementioning
confidence: 99%
“…There has been little work on consequences of gender attitudes and stereotypes, and most of it was conducted on children and focused on outcomes other than psychosocial adjustment. For example, children who held genderstereotyped beliefs had limited interests and skills and difficulty remembering events inconsistent with their beliefs (Bigler & Liben, 1990;Bussey & Bandura, 1992;Martin & Halverson, 1983).…”
Section: Introductionmentioning
confidence: 99%